Defining the relationship of crime and terrorism - Shelley, Louise (Henry Stewart Talks, 2008)
Origins of crime-terror interaction, Transnational crime and terrorism, Old vs. new organized crime, Crime and new wars, Moving beyond narco-terrorism, Crime and terror: challenges to the state and legal process, Arguments for nexus, convergence and symbiosis, Points of interaction, Service functions provided by crime groups, How to tackle crime-terror nexus, Problems of law enforcement
Archived at 2022/04/03